Minimum Variance Linear Receiver for Interference Rejection in Space-Time Block Code Communications - Beheshti, Ali Mohammad (My University, 2004)
In this thesis, we consider a wireless communication system which has several transmitters (users), and one receiver (base station). The goal is to extract the data from the desired transmitter, we have to combat noise and interferences from the other transmitters (users). In order to decrease the probability of error we use space diversity; therefore the desired transmitter (user) and receiver (base station) are equipped with arrays of antennas.
We use Orthogonal Space-Time Block Codes (OSTBC) because they reach full diversity-gain. Furthermore, these codes enable us to introduce a new linear-receiver, which suppresses the interference and decodes the received data simultaneously.
The proposed receiver is designed by enforcing an underline operator on the vector of the received data. We minimize the output power subject to a constraint which preserves a unity gain for all symbols in the desired transmitter's block of data, at the same time, the intra block interference (self-interference) for the desired transmitter (user) is completely suppressed.
Simulation results show that the proposed method has substantially lower symbol error rate compared to the matched filter receiver and linear receiver presented by Naguib and Seshadri. Note that in absence of interference, our receiver simplifies to the matcher filter, which is the Maximum Likelihood receiver for a single user MIMO system using Orthogonal Space-Time Block Codes.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering